'I don't know why we have gated developments in Ceres': crime, fear, and gated developments in nonmetropolitan towns in the Western Cape province, South Africa. Issue 3 (3rd July 2022) - Spocter, Manfred
ABSTRACT: Gated developments are a ubiquitous feature of the post-apartheid urban landscape. However, there is a dearth of research on gated developments in nonmetropolitan areas. A gated development security level index was created to assist in the investigation of the relationship between crime levels and differing levels of securedness of gated developments within small towns. The town of Ceres is case studied to explore the nexus of crime, violence, and fear as reasons why residents live in gated developments. The growth of gated developments in nonmetropolitan settlements could lead to the fragmentation of small-town built environments, mirroring larger urban places.